Geological and Morphometric Characteristics of Quaternary Pyroclastic Aquifers in Salak and Pangrango Stratovolcano. - Bayu Nugraha; Mohammad Ghozi; Arif Fadillah; Azwar Satrya Muhammad; Teuku Yan Waliyana Muda Iskandarsyah; Nathalie Dörfliger; Valérie Plagnes; Hendarmawan Hendarmawan (UIR PRESS, 2023)
Indonesia is located in a subduction zone formed by the collision of continental and oceanic plates. Many volcanoes form as a result of these conditions along the arc. Springs on the volcano's slopes are widely used for domestic, irrigation, and industry water use. Investigating the characteristics of aquifers and springs is essential to ensure groundwater sustainability by providing a robust geological framework. Meanwhile, groundwater in a volcanic geological setting has good quality characteristics because of its occurrence process, which interacts with many minerals in pyroclastic rocks that act as aquifers. The study area is located in the Lido Catchment Area (LCA), which is situated between two distinct volcanic slopes. Geological and morphometric analysis at LCA is the basis of important information relating to its hydrogeological systems. The analysis of thin rock sections and parameters of the physical properties of water in groundwater springs supports our research. We applied a comprehensive geological and morphometric analysis to obtain detailed information about the aquifer. This study aimed to determine the characteristics of aquifers in pyroclastic rocks and their relationship to the formation of springs. From the research conducted, the characteristic of water can be distinguished based on the geological conditions of its constituents. There are 6 different lithological characteristics in the study area: polymictic breccia, monomictic breccia, lapilli, lapilli tuff, coarse tuff, and fine tuff. From the lithology variations obtained, breccia, lapilli, and coarse tuff can play a good role as aquifers. Geological correlations and groundwater systems in the study area show groups of superficial, mixed, and alteration springs. The system of water flows in aquifers through inter-grains or rock fractures. The types of springs in LCA are dominated by depression and fracture types. These results are fundamental information for understanding hydrogeological systems in future volcanic geological settings.